Associations of serum folate and vitamin C levels with metabolic dysfunction-associated fatty liver disease in US adults: A nationwide cross-sectional study - Yuqi Jiang; Huanyi Cao; Xingying Chen; Genfeng Yu; Cheng Song; Hualin Duan; Feng Tian; Heng Wan; Heng Wan; Jie Shen; Jie Shen (Frontiers Media S.A., 2022)
BackgroundClinical research results on the relationship between folate and non-alcoholic fatty liver disease are contradictory. Metabolic dysfunction-associated fatty liver disease (MAFLD) is a recently proposed concept. Evidence about the relationship between serum folate and MAFLD, especially considering the status of serum vitamin C, is scarce. This study was aimed to investigate the association of serum folate levels with the prevalence of MAFLD, and further to analyze the potential impact of serum vitamin C status on their association.MethodsTotally 2,797 participants from National Health and Nutrition Examination Survey (NHANES) 2017-2018 were included. Vibration-controlled transient elastography was used to detect liver steatosis and fibrosis. Participants were divided in groups based on the tertiles of serum folate or vitamin C, and the serum folate or vitamin C level in T1 was low. Logistic regression analysis in the complex sample module was performed to illustrate the association of serum folate levels with the prevalence of MAFLD. Stratification analysis by serum vitamin C status was performed as well.ResultsCompared with the serum folate levels of T1 group, participants in the T3 group had 47.9% lower risk of MAFLD [OR = 0.521 (95% CI: 0.401-0.677)]. However, when participants were stratified by serum vitamin C levels, there was no association between the serum folate levels and MAFLD in the T1 or T2 group. Among participants in the T3 group of vitamin C status, participants in the T3 group of serum folate had a 63.6% lower risk of MAFLD compared with the T1 group [OR = 0.364 (95% CI: 0.147-0.903)].ConclusionsHigh serum folate level is associated with lower prevalence of MAFLD, especially in participants with sufficient vitamin C.